Case Study on The Operational Optimization of The Financial Shared Services Center at Huahe Real Estate - Ling, Meng (Transactions on Economics, Business and Management Research, 2024)
During the period of reform and opening-up in China, the real estate industry has experienced rapid development. Since the housing system reform began in 1998, an increasing number of enterprises have entered the real estate sector. Most well-known large real estate companies emerged during this time. Until 2007, the real estate market was in its "golden era," where companies could enhance their profits solely through land appreciation. However, as more companies entered the market, available land for construction became scarcer, competition intensified, and the government's regulatory policies on the real estate industry increased, making it more challenging for real estate companies to earn profits as easily as before. In recent years, the government has introduced the concept of "housing is for living, not for speculation," strengthening its control over the real estate sector. Consequently, real estate companies have begun to transform their profit models in an effort to continue generating profits.This article analyzes the operations of the financial shared services center at Huahe Real Estate and identifies issues such as a high core business order cancellation rate, low internal operational efficiency, a high employee turnover rate at the shared center, and problems related to information technology. The third section analyzes the causes of these issues from both internal and external perspectives. Internally, the factors include strategic structure, business processes, personnel management, and information systems. Externally, the primary causes are related to national policies and technological changes. The fourth section proposes corresponding policy recommendations based on the identified issues and their causes. It is hoped that this analysis will provide insights for the ongoing operations of the financial shared services center at Huahe Real Estate, as well as offer case support for other real estate companies looking to establish financial shared services centers.